Insect herbivores associated with Senecio pterophorus and Senecio inaequidens at Butterworth, South Africa - Muwanga-Zake, Johnnie Wycliffe Frank (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1995)
This study lists and compares insect herbivores of Senecio inaequidens and of Senecio pterophorus around Butterworth by 18 Tables and 38 Figures. The two plant species are widely distributed around Southern Africa. Samples were taken during a month of each of the four main seasons of the year, which in Butterworth did not show much difference in temperature. The two plant species shared generalist insect herbivores most of which were also on other surrounding plant species. The population of most of the herbivores was affected by the seasons while the two plant species were not seasonal, thus the correlation between insect herbivores and the two plant species was not significant. The heavier, and apparently chemically protected species, Senecio pterophorus, accommodated borers and supported a wider variety of but fewer individual insects. Senecio pterophorus could be having more defences but had more serious herbivores. There were no serious insect herbivores that could control the abundance of the two plant species around Butterworth. Anatomical differences between S. pterophorus and S. inaequidens could be highlighted by the kind and number of insect herbivores found upon them. Similarities were more difficult to identify through studying their insect herbivores. The biology of one serious weed, Lixus sp., on Senecio pterophorus was studied in more detail. The life cycle of the weevil was found to be synchronised with that of the host. This weevil shared the stems with other species of weevils with no indication of competition.
Keywords: Senecio -- South Africa -- Eastern Cape -- Butterworth; Insect-plant relationships -- South Africa -- Eastern Cape -- Butterworth; Insects -- South Africa -- Eastern Cape -- Butterworth; Host plants; Insects -- South Africa -- Eastern Cape -- Butterworth; Food Lixus -- biology; Insect-plant relationships